Animation of Graphic Symbols Representing Verbs and Prepositions: Effects on Transparency, Name Agreement, and Identification. - Schlosser, Ralf W.; Shane, Howard; Sorce, James; Koul, Rajinder; Bloomfield, Emma; Debrowski, Lisa; DeLuca, Tim; Miller, Stephanie; Schneider, Danielle; Neff, Allison (Journal of Speech, Language & Hearing Research, 2012)
Purpose: The effects of animation on transparency, name agreement, and identification of graphic symbols for verbs and prepositions were evaluated in preschoolers of 3 age groups. Methods: A mixed-group design was used; in each age group, half of the children were randomly allocated to 1 of 2 orders of symbol formats. The 52 children were asked to guess the meaning of symbols and to identify a target symbol among foils given the spoken label. Results: Animated symbols were more transparent than static symbols, although this was more pronounced for verbs. Animated verbs were named more accurately than static verbs, but there was no difference between animated and static prepositions. Verbs were identified more accurately compared with prepositions, but there was no difference between symbol formats. Older children guessed, named, and identified symbols more effectively than younger children. Conclusion: Animation enhances transparency and name agreement, especially for verbs, which reduces the instructional burden that comes with nontransparent symbols. Animation does not enhance identification accuracy. Verbs are easier to identify than prepositions. A developmental effect was observed for each measure. Limitations and implications for future research are discussed.